Method of approach in physical geography and its role in studying geosistem’s structure (Journal of Geography and Environmental Management, 2019)
The study of the system is an expression of the fundamental principle of dialectical materialism ofuniversal interconnection and interaction of objects and phenomena of nature. Occurrence and formationof a systematic approach in modern science is related toan objective need for ordering and understandingof a variety of new evidence on the natural objects, the study of their internal and external communicationsin order to syn the size natural representation sabout the environment, about the construction ofa coherentpicture of wildlife and forecasting its development. In physical geography methodological understandingof the system as integrity, determination and a systematic approach, as a principle of study and researchfacilities as system sare common.